Curcumin Attenuates Doxorubicin-Induced Cardiac Oxidative Stress and Increases Survival in Mice - Felipe S. Arruda; Fernanda D. Tomé; Anália C. Milhomem; Pablo I. R. Franco; Allisson B. Justino; Rodrigo R. Franco; Erica C. Campos; Foued S. Espindola; Danilo F. Soave; Mara Rubia N. Celes (MDPI AG, 2024)
Doxorubicin (DOX) is a potent chemotherapeutic agent used to treat multiple types of cancer, but its clinical application is limited by cardiotoxicity, mainly due to oxidative stress. Curcumin (CUR) is a natural polyphenolic compound with strong antioxidant properties, but its potential protective effects against DOX-induced cardiotoxicity need further investigation. This study aimed to evaluate CUR's efficacy in mitigating DOX-induced oxidative stress in the hearts of BALB/c mice. Mice received a DOX dose of 9 mg/kg or 16 mg/kg; half of the mice received daily doses of 100 mg/kg CUR for 15 days. Survival analysis, histopathological examination, and oxidative stress markers were assessed to determine the cardioprotective effects of CUR. Results showed that CUR significantly reduced oxidative damage and improved survival rates, particularly at the lower DOX dose (9 mg/kg). Mice treated with DOX-9 mg/kg plus CUR showed improved health conditions and reduced levels of reactive oxygen species (ROS), lipid peroxidation, sulfhydryl production, and protein carbonylation. Histopathological analysis confirmed reduced cardiac tissue damage. In conclusion, CUR combined with a lower dose of DOX effectively reduces oxidative stress and cardiac injury, enhancing survival in BALB/c mice. These findings suggest that CUR is a promising adjunct therapy to mitigate DOX-induced cardiotoxicity, potentially improving the DOX therapeutic index in cancer treatment.